Does Service FDI Locate Differently to Manufacturing FDI? A Regional Analysis for Great Britain. Issue 12 (1st December 2016) - Jones, Jonathan; Wren, Colin
Abstract : Jones J. and Wren C. Does service FDI locate differently to manufacturing FDI? A regional analysis for Great Britain, Regional Studies . This paper analyses the location of foreign direct investment (FDI) in services at the NUTS-2 region level for Great Britain over 1996–2005, covering the period of growth in FDI. It finds strong differences in service FDI location compared with manufacturing FDI. Unlike manufacturing, service FDI location is determined at no higher than the NUTS-2 region level, while it is more dynamic and converging to the larger markets. A similar pattern is found for the services that are most forward-linked to manufacturing industries. The paper concludes that access to final consumer demand is important for service FDI, with implications for UK regional policy.